2003
DOI: 10.1046/j.1365-2516.2003.00769.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of full‐length and B‐domain deleted factor VIII for prophylaxis – a meta‐analysis

Abstract: Recently reported data suggest the possibility of differences in clinical efficacy between full-length factor VIII (FL-FVIII) and B-domain deleted recombinant factor VIII (BDD-rFVIII). To address this question, we conducted a meta-analysis of studies reporting the incidence of bleeding under prophylaxis, as well as studies of FL-FVIII and BDD-rFVIII half-life. The pooled cumulative weekly prophylactic dose of BDD-rFVIII (81.3 +/- 13.8 IU kg(-1) week(-1)) was greater by 36% (P = 0.11) than that of FL-FVIII (60.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 57 publications
2
43
1
Order By: Relevance
“…Keywords: factor VIII, haemophilia A, haemorrhage, half-life, meta-analysis, protein engineering We earlier reported the results of a meta-analysis suggesting reduced haemostatic efficacy during prophylaxis and shortened half-life of B-domain deleted factor VIII (BDD-rFVIII) when compared with fulllength (FL)-FVIII [1]. We included 13 studies in the meta-analysis and extracted data on annual incidence of bleeding episodes during prophylaxis.…”
mentioning
confidence: 99%
“…Keywords: factor VIII, haemophilia A, haemorrhage, half-life, meta-analysis, protein engineering We earlier reported the results of a meta-analysis suggesting reduced haemostatic efficacy during prophylaxis and shortened half-life of B-domain deleted factor VIII (BDD-rFVIII) when compared with fulllength (FL)-FVIII [1]. We included 13 studies in the meta-analysis and extracted data on annual incidence of bleeding episodes during prophylaxis.…”
mentioning
confidence: 99%
“…Functional activity of FVIII secreted in culture medium from the cells carrying the vector as confirmed by a chromogenic assay, (COATEST VIII: C/4, Chromogenix) indicated that even full-length FVIII is processed in these B-cell lines. Recent prophylaxis analysis comparing the effectiveness of full-length and B-domaindeleted factor VIII indicates that bleeding may occur more frequently in patients receiving B-domain-deleted recombinant FVIII than full-length FVIII and suggests the effectiveness and stability of the full-length version [16]. Although a 10% increase in FVIII level in our in vitro cell model is rather modest, clinical application of this technology would be through a hematopoietic stem cell transplant.…”
Section: Discussionmentioning
confidence: 89%
“…Accelerated inactivation of BDD-rFVIII, as well as accelerated activation by thrombin, would necessitate either higher doses or more frequent dosing. A 2003 meta-analysis did demonstrate increased bleeding incidence associated with the use of BDD-rFVIII compared with full-length FVIII for prophylaxis [40].…”
Section: Fate Of Factor VIII In Circulationmentioning
confidence: 99%
“…While some explanatory factors, such as ABO blood group, have been identified, the reasons for this variability are still poorly understood. A metaanalysis of 27 pharmacokinetic studies suggested that BDD-rFVIII may have a shorter circulating half-life than full-length FVIII [40]. An acknowledged limitation of the meta-analysis was the scarcity of available data derived from direct comparison between FVIII types in the same study.…”
Section: Fate Of Factor VIII In Circulationmentioning
confidence: 99%